Characteristics of sleep disorders in patients with chronic back pain - Daniil K. Vinogradov; O. B. Doronina (Клиническая практика, 2019)
Background. Insomnia is considered a risk factor for the frequency of pain, however, no reliable studies with a comprehensive analysis of the objective polysomnography data have been conducted so far.